Micro-Tracked CPV Can Be Cost Competitive With PV in Behind-The-Meter Applications With Demand Charges - Wright, David J.; Badruddin, Sana; Robertson-Gillis, Cameron (Frontiers in Energy Research, 2018)
Micro-tracked CPV, in which cells move relative to fixed concentrating optics, allows CPV to be deployed in the same manner as fixed PV modules. Behind-the-meter applications in locations where there is a land/roof area cost for the space occupied by the modules confers a cost advantage to CPV compared to PV. The primary objective of the present paper is to estimate target prices below which CPV has a competitive advantage over PV. We analyse PV and CPV microgrids, optimizing the scheduling of power into and out of the battery in order to achieve the maximum savings compared to purchasing grid power. We then choose the battery capacity that maximizes the internal rate of return (IRR) on the PV microgrid. The CPV target price is the price that gives a CPV IRR that matches the PV IRR. The analysis is performed for 3 battery prices and 3 load profiles, in 3 cities in southwestern USA with different irradiance profiles, different time-of-use commercial electricity prices together with different demand charges levied on peak hour consumption each month. Land prices from 0/m2 to 400/m2 are analysed, representing the range from the urban fringe to commercial office parks. The target CPV prices obtained are found to depend on the land price and on the ratio of CPV to PV annual energy yield (REY), but are insensitive to battery prices, load profiles, current electricity tariffs and future trends in electricity tariffs. Modesto, CA has a REY of 1.10 and an average target CPV price from 1.86/W at zero land price to 3.53/W at 400/m2. Lancaster, CA with a REY of 1.26 has corresponding target CPV prices from 2.14/W to 4.23/W. In Las Vegas, NV, (REY = 1.27) the target CPV price is 2.13/W at a land price of zero, but at higher land prices the IRR is insufficient for solar power to be deployed. These target CPV prices correspond with current estimates of pedestal-tracked CPV of 2.4/W to 3.3/W and indicate that it is realistic to expect micro-tracked CPV to be cost competitive with PV in some urban areas in southwestern USA.